2010
DOI: 10.1371/journal.pone.0013916
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Human Serum Antibody Responses Elicited by Three Leading HIV Vaccines Focusing on the Induction of Env-Specific Antibodies

Abstract: In the current report, we compared the specificities of antibody responses in sera from volunteers enrolled in three US NIH-supported HIV vaccine trials using different immunization regimens. HIV-1 Env-specific binding antibody, neutralizing antibody, antibody-dependent cell-mediated cytotoxicity (ADCC), and profiles of antibody specificity were analyzed for human immune sera collected from vaccinees enrolled in the NIH HIV Vaccine Trial Network (HVTN) Study #041 (recombinant protein alone), HVTN Study #203 (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 37 publications
3
44
0
Order By: Relevance
“…The tier 2 neutralizing capacity of the elicited sera did not appear to be dependent upon priming with cell surface-cleaved JRFL Env, as priming with soluble trimer DNA also generated such activity. Consistent with these data, previous studies have demonstrated improved neutralization following HIV-1 Env DNA prime-protein boost regimens compared to inoculation of Env gp120 protein alone (51)(52)(53)(54)(55). In the more sensitive A3R5 assay, we observed high to modest tier 2 neutralization of all clade B and clade C isolates tested in the serum of most trimer-inoculated animals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The tier 2 neutralizing capacity of the elicited sera did not appear to be dependent upon priming with cell surface-cleaved JRFL Env, as priming with soluble trimer DNA also generated such activity. Consistent with these data, previous studies have demonstrated improved neutralization following HIV-1 Env DNA prime-protein boost regimens compared to inoculation of Env gp120 protein alone (51)(52)(53)(54)(55). In the more sensitive A3R5 assay, we observed high to modest tier 2 neutralization of all clade B and clade C isolates tested in the serum of most trimer-inoculated animals.…”
Section: Discussionsupporting
confidence: 90%
“…These other DNA delivery means prime B cell responses that can be boosted by subsequent protein inoculation, but with lower titers than detected here. That two proteins in adjuvant elicited similar binding titers to a single boost of protein primed by DNA suggested that a DNA prime was essentially equal to a protein prime at the quantitative level of binding antibodies, as has been observed in several other studies using a similar DNA prime-protein boost format (51)(52)(53)(54)(55).…”
Section: Discussionsupporting
confidence: 62%
“…Inducing broadly neutralizing antibodies by vaccination has proven to be difficult. Most vaccines tested to date, including the moderately protective RV144 vaccine regimen, elicited tier 1 but not tier 2 neutralizing responses (38,47,48). As passive immunization studies have shown that neutralizing antibodies are able to protect from SHIV infection (50,51), inducing this immune response is an important goal for an HIV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…boost regimens. Although most HIV Env vaccines tested to date have been able to induce strong systemic binding antibody responses, only tier 1 and occasionally tier 2 neutralization responses have been elicited through vaccination (38,47,48). Thus, inducing potent, broadly neutralizing antibody responses remains an important goal for future HIV vaccine candidates.…”
Section: Systemic and Mucosal T/f Env Immunization Of Lactating Rhesumentioning
confidence: 99%
“…This strategy did not result in the induction of broad heterologous NAbs, but this may have been due to the vaccine delivery system used and/or to the fact that sequences were derived from an SHIV-infected macaque after less than 2 years of infection. Naked DNA plasmids have long been considered a weak delivery system to induce protective immune responses (30,31), but recent studies showed that DNA prime-protein boost approaches can induce neutralizing antibodies in rabbits and in humans (52,53). Additional experiments are in progress using env variants cloned from the plasma of HIV-infected human subjects who developed more potent NAbs than did macaque A141 to determine the broader utility of this approach, as well as to further explore the use of key individual variants that arise during infection as immunogens.…”
Section: Discussionmentioning
confidence: 99%